Highly efficient Agrobacterium rhizogenes-mediated hairy root transformation for gene editing analysis in cotton - Zhou, Lili; Wang, Yali; Wang, Peilin; Wang, Chunling; Wang, Jiamin; Wang, Xingfen; Cheng, Hongmei (Frontiers in Plant Science, 2022)
CRIPSR/Cas9 gene editing system is an effective tool for genome modification in plants. Multiple target sites are usually designed and the effective target sites are selected for editing. Upland cotton (Gossypium hirsutum L., hereafter cotton) is allotetraploid and is commonly considered as difficult and inefficient to transform. Therefore, it’s important to quickly identify the feasibility of target sites. In this study, Agrobacterium rhizogenes-mediated hairy root method was optimized to detect the feasibility of the target sites designed in cotton phytoene desaturase (GhPDS) gene. A. rhizogenes showed the highest hairy root induction (30%) when the bacteria were cultured until OD600 reached to 0.8. This procedure was successfully applied to induce hairy roots in the other three cultivars (TM–1, Lumian–21, Zhongmian–49) and the mutations were detected in GhPDS induced by CRISPR/Cas9 system. Different degrees of base deletions at two sgRNAs (sgRNA5 and sgRNA10) designed in GhPDS were detected in R15 hairy roots. Furthermore, we obtained an albino transgenic cotton seeding containing CRISPR/Cas9-induced gene editing mutations in sgRNA10. The hairy root transformation system established in this study is sufficient for selecting sgRNAs in cotton, providing a technical basis for functional genomics research of cotton.